Role of Exosomes in Brain Diseases - Zhang, Nan; He, Fengling; Li, Ting; Chen, Jinzhi; Jiang, Liping; Ouyang, Xin-Ping; Zuo, Lielian (Frontiers in Cellular Neuroscience, 2021)
Exosomes are a subset of extracellular vesicles that act as messengers to facilitate communication between cells. Non-coding RNAs, proteins, lipids, and microRNAs are delivered by the exosomes to target molecules (such as proteins, mRNAs, or DNA) of host cells, thereby playing a key role in the maintenance of normal brain function. However, exosomes are also involved in the occurrence, prognosis, and clinical treatment of brain diseases, such as Alzheimer's disease, Parkinson's disease, stroke, and traumatic brain injury. In this review, we have summarized novel findings that elucidate the role of exosomes in the occurrence, prognosis, and treatment of brain diseases.